Implementasi Modifikasi Penggunaan Energi Protokol Routing SPIN pada Wireless Sensor Network - Antarif Ekadhia Cahyadi; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Wireless Sensor Network (WSN) is a collection of sensor nodes with limited energy resources that are distributed in a certain area so as to create a network architecture that is connected to each other. With the limited energy resources available at each node, it becomes a challenge for the implementation of the architecture. In an effort to save energy, one of the ongoing studies is to make WSN devices last a long time. One of the efforts to save energy is to choose a routing protocol that can save energy. One of the protocols developed by experts based on meta-data for ideal lossless networks is the Sensor Protocol for Information via Negotiation (SPIN) protocol. However, the SPIN protocol itself still has problems that the protocol has not been able to solve. One way to solve this problem is to modify the SPIN protocol itself. Modifying the protocol is expected to extend the lifetime of a node, by applying randomized packet dropping modifications to the SPIN routing algorithm and using energy detection in the OMNET++ simulation program so that it can save energy consumption and extend the active life of nodes. In this study, the results achieved to extend the lifetime of a small number of nodes, while the larger the number of nodes the energy difference becomes less different.